ANALISIS OVERALL EQUIPMENT EFFECTIVENESS (OEE) DAN SIX BIG LOSSES PADA MESIN WASHING VIAL DI PT. XYZ - Muhamad Dipa; Fitria Dewi Lestari; Muhamad Faisal; Muhamad Fauzi (LPPM Universitas Bina Bangsa, 2022)
PT. XYZ is one of the pharmaceutical companies that always make continuous improvements. Based on observations at the company, there is a decrease in the performance of the Washing Vial machine used for the washing and sterilization process of the vial. This problem causes a large number of rejected products so that production targets are not achieved. This study aims to calculate the OEE (Overall Equipment Effectiveness) and Six Big Losses values of gilowy machines so that they can be known the largest losses incurred by the machine. Based on calculations obtained OEE (Overall Equipment Effectiveness) value of 53.68% with Availability of 63.36%, Performance Ratio of 87.21% and Quality Ratio of 97.59%. The calculation of the Six Big Losses is equipment failure loss of 36.64%, Setup Time Losses of 17.07%, Reduced Speed Losses of 8.36%, Idle and Minor Stoppage of 40.25%, Defect Losses of 1.36% and Reduced Yield Loss of 0%. From these results show Idle and Minor Stoppage to be the biggest factor losses that occur in the Gilowy machine